Dynamic background on formation, evolution, and later reformation of the Late Paleozoic–Early Mesozoic Basin in Songliao and its significance for hydrocarbon exploration - Song, Lijun; Ruan, Yongqi; Sun, Yonghe; Xie, Fenquan; Li, Junlong; Yuan, Yulong (Frontiers in Earth Science, 2023)
Located on the Songnen block in the Northeast Asian block group, the Songliao Basin is sandwiched by three major plates of Siberia, North China and the Pacific Ocean. The recognitions on the basin properties, the dynamic process of formation, evolution and late reformation of Late Paleozoic-Early Mesozoic Basin (LP-EMB) are always controversial, which suffered from intense multi-stage, and various types of late reformation. On the basis of previous researches on the regional tectonic geological background, combining with petro-chemical and chronological data from core samples and seismic data, the basin attribute, evolution process and late reformation of the LP-EMB and its dynamic environments have been deeply analyzed. Since the Late Paleozoic, it has successively experienced the development of the late Hercynian to early-middle Indosinian rifts and the subsequent multi-stage superimposed transformation stages, which can be divided into the near north-trending thrust reformation in late Indosinian, near west-trending thrust reformation in early Yanshanian, the differential extensional reformation in early Late Yanshanian, the strike-slip shearing and deep burial reformation in middle Late Yanshanian, strike-slip compression fold transformation in late Late Yanshanian to early Himalayan. The formation of LP-EMB was mainly controlled by the back-arc extension caused by the sub-duction and retreat of the paleo-Pacific plate and partly by closure of Paleo-Asian Ocean among the North-China Plate and the Northeast China micro-block group. The later reformation stages were closely related to the collision extrusion, strike-slip activity and the deep mantle activity caused by either the relative convergence movement between Songnen and other micro-blocks in the Northeast China micro-block group or the remote collision effect of the Northeast China micro-block group and the surrounding plates. The inner fault zone (body), which was formed by multi-phase fault cutting, and the top weathering and denudation unconformity surface, are the potential sites for hydrocarbon accumulation, of which the natural gas was transported along the fault and fracture belt into the weathering crust and the inner fracture zone in the Upper Paleozoic-Early Mesozoic(LP-EM). This study adds significantly our knowledge of the tectonic evolution and gas exploration of the Songliao Basin.